(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
Endemic goiter remains one of the most common thyroid pathologies in regions with iodine deficiency. A visiting nurse, as a key link in primary health care, plays an important role in the prevention, early diagnosis and monitoring of patients with endemic goiter. This article analyzes epidemiological data on the prevalence of the disease, its causes, clinical manifestations and strategic aspects of nursing care in the fight against this disease.